Observer-based event triggering security load frequency control for power systems involving air conditioning loads - Xiaoming Wang; Yunlong Bai; Zhiyong Li; Wenguang Zhao; Shixing Ding (Electronic Research Archive)
This paper presents a power system frequency control strategy that integrates an observer-based event-triggered mechanism (ETM) to defend against denial-of-service (DoS) attacks and accommodates the integration of renewable energy sources. The proposed strategy incorporates demand response by enabling air conditioning loads (ACs) to participate in frequency regulation, thereby enhancing system flexibility and stability. To address the challenges posed by limited network bandwidth and potential message blocking, the ETM minimizes communication while defending against DoS attacks. The stability of the closed-loop system is guaranteed by deriving an $ H_{∞} $ stability criterion using the Lyapunov–Krasovskii function method, with controller parameters determined through linear matrix inequalities (LMIs). A two-area power system simulation is conducted to validate the feasibility and effectiveness of the proposed approach, demonstrating its ability to maintain stable frequency control under cyber-attack scenarios and varying renewable energy contributions.